Rainfall distribution in Yamuna catchment and quantitative estimation of heavy rainfall in related synoptic situations - DUGGAL, Y. M.; SAGAR , H. S.; MITTAL, A. K. (MAUSAM, 1992)
A study of rainfall over Yamuna catchment from its origin upto Delhi for the period from 1976to 1990 IS made with an attempt to understand the fine distribution of rainfall in different ranges over the catch-ment for the flood operational period from .1 June to 15 October. The study of associated synoptic situations for heavy rainfall activity in the catchment is made for synoptic typing. Synoptic empirical diagrams have been developed for estimation of average isohyetal rainfall over the catchment from estimation of moisture transport.